2012
DOI: 10.1038/clpt.2012.54
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pharmacovigilance-Related Adverse Events Using Electronic Health Records and Automated Methods

Abstract: Electronic health records (EHRs) are an important source of data for detection of adverse drug reactions (ADRs). However, adverse events are frequently due not to medications but to the patients’ underlying conditions. Mining to detect ADRs from EHR data must account for confounders. We developed an automated method using natural-language processing (NLP) and a knowledge source to differentiate cases in which the patient’s disease is responsible for the event rather than a drug. Our method was applied to 199,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 45 publications
(42 reference statements)
2
74
0
1
Order By: Relevance
“…While NLP is still evolving in healthcare, it has the potential to greatly expand the utility of EMRs for outcomes research. Researchers are clearly making progress in this domain, as a post-hoc search for NLP-based outcomes studies published since the review cutoff date, 1 January 2012, identified six additional outcomes methodology-based studies that report on the use of NLP for identifying/classifying patients and outcomes measures [114,115,[117][118][119][120].…”
Section: Expert Commentarymentioning
confidence: 99%
“…While NLP is still evolving in healthcare, it has the potential to greatly expand the utility of EMRs for outcomes research. Researchers are clearly making progress in this domain, as a post-hoc search for NLP-based outcomes studies published since the review cutoff date, 1 January 2012, identified six additional outcomes methodology-based studies that report on the use of NLP for identifying/classifying patients and outcomes measures [114,115,[117][118][119][120].…”
Section: Expert Commentarymentioning
confidence: 99%
“…Examples of the combined use of standard NLP and text-and data-mining are found in [139][140][141] where cTAKES is used with Boolean logic to perform phenotyping and to extract drug-side effects. MedLEE was applied for: 1) adverse drug reaction (ADR) signaling, where the association between a drug and an ADR was obtained by using disproportionality analysis [142,143] or Boolean logic [144], or by building and analyzing statistical distributions of concepts (i.e., diseases, symptoms, medications) extracted from the narrative text [145]; 2) EHR-data driven phenotyping using Boolean logic on MedLEE-extracted concepts [136,146]; 3) automated classification of outcomes from the analysis of emergency department computed tomography imaging reports using machine learning methods, such as decision trees [147]. MetaMap has been used with logistic regression in [148] to discover inappropriate use of emergency room based on information on drugs, psychological characteristics, diagnoses, and symptoms.…”
Section: F Extraction Of Information From Unstructured Clinical Datamentioning
confidence: 99%
“…[11] Drug-ADEs association rules have been used to assess associations between drugs and symptoms. [9] Medications are prescribed mostly in PHC, yet information on ADEs from this setting is scarce. In this paper, we want to bridge the gap and to highlight the potential of IT in facing this challenge.…”
Section: Introduction 11 Introduction On Using Information Technologmentioning
confidence: 99%
“…[8] What makes the use of this method difficult is the fact that ADEs are usually contextdependent, that means that they are caused by disease-related and patient-related, rather than drug-related conditions. [9] In order to make detection of ADEs from eHRs much easier, new IT approaches have emerged, putting attention on the precision and strength of ADEs signals generated from medical data. [8] To further strenghten the efforts on ADEs information collection, some supplement data sources have been used to complement the standard ones, including drug labels, biomedical literature and biomedical knowledge.…”
Section: Introduction 11 Introduction On Using Information Technologmentioning
confidence: 99%